2022
DOI: 10.1039/d2ta04788h
|View full text |Cite
|
Sign up to set email alerts
|

Screening interface passivation materials intelligently through machine learning for highly efficient perovskite solar cells

Abstract: Intelligently screening the passivation materials is critical to improving power conversion efficiency (PCE) of the perovskite solar cell (PSC), while it is still lacking. Herein, machine learning is employed to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…Massuyeau et al 2022 [198] Perovskite Liu et al 2022 [166] PCE LR, RF, XGBoost ANN Experiment ML was employed to predict the relation between the PCE and interface passivation material at the atomic level, as well as rapidly screen interface materials for PSCs. The predictions are further validated using DFT and experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Massuyeau et al 2022 [198] Perovskite Liu et al 2022 [166] PCE LR, RF, XGBoost ANN Experiment ML was employed to predict the relation between the PCE and interface passivation material at the atomic level, as well as rapidly screen interface materials for PSCs. The predictions are further validated using DFT and experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al [ 166 ] used ML to screen interfacial materials by studying the correlation between PCE and interfacial passivation materials at the atomic level (Figure 7d). Based on SHAP values, feature importance, and correlation analysis, the most critical 15 features were selected from over 300 features.…”
Section: Implementation Of ML For the Advancement Of Efficient And St...mentioning
confidence: 99%
“…Furthermore, recently, Wu Liu et al adopted ML to screen perovskite/hole transport layer interface materials. 30 This work demonstrated that ML can be effectively used to investigate passivation materials without knowledge of chemistry and resulted in reference functional groups for the synthesis of new passivation materials. However, guidelines for the screening of passivation materials in p–i–n type PSCs are still lacking.…”
Section: Introductionmentioning
confidence: 91%
“…In a recent study, Liu et al implemented ML for analyze the impact of interfacial modifiers over the device performance. [ 136 ] They have collected the data from 100 materials that are used as modifiers at the perovskite/HTL interface. On the basis of collected data, an RF model was developed, and their model predicted with an RMS value of 0.7%.…”
Section: Various Applications Of ML In Pscsmentioning
confidence: 99%